PENGARUH PENGGUNAAN SARI BUAH PEPAYA MUDA TERHADAP KEEMPUKAN, pH, DAN DAYA IKAT AIR DAGING ITIK PETELUR AFKIR - Triyono Triyono; Rr. Riyanti; Veronica Wanniatie (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2021)
This research was aimed to determine the effect of unripe papaya extract on tenderness, pH value, and water holding capacity (WHC) of laying duck meat. This research was conducted in January 2020 in Laboratory of Animal Production of Animal Husbandary Department and in Laboratory of Agricultural Technology, Faculty of Agriculture, Lampung University. The materials of this research were 20 pieces of laying duck thigh meat. The research used Completely Randomized Design (CRD) with 4 treatments and 5 reaplications, i.e. duck thigh meat marination with 0% of unripe papaya extract (P0), with 10% of unripe papaya extract (P1), with 20% of unripe papaya extract (P2), and with 30% of unripe papaya extract (P3). The observed variables were tenderness, pH value, and WHC of laying duck meat. The obtained data was analyzed by using variance analysis at 5% level of significance, and if the results had significant effect, then were tested further using Least Significant Difference (LSD) test. The result of variance analysis indicated that marination of laying duck meat with different percentage of unripe papaya extract affected on tenderness (P<0,05), but it did not affect on pH value and WHC of laying duck meat. Keywords: Laying duck meat, pH value, Tenderness, Unripe papaya extract, Water Holding Capacity (WHC)